From STEAM to CHEER: A Case Study of Design Education Development in Taiwan - Chinlon Lin; Jianping Huang; Rungtai Lin (MDPI AG, 2021)
The purpose of this study is to provide other developing countries in the region a reference on the successful design education reformation in Taiwan. The study first reviews Taiwan's economic and design development to show their interconnection with local culture and the global market. Next, the study explores Taiwan's design education development which transforms from adopting STEM (science, technology, engineering, mathematics) to STEAM (science, technology, engineering, art, mathematics) in secondary school, and understands how it overcomes challenges by the help of both public and private sectors. Last, a conceptual framework is proposed to present and study Taiwan's design education development. The result from case studies validates that STEAM can reach SAD (science, arts, and design) in higher education and CHEER (collaboration, humanity, empathy, ecology, and renaissance) in design practice. Therefore, the result and implications provided by this study can serve as a reference for other countries in the region who share similar cultural and socioeconomic development and future goals as Taiwan.